Analisis Prediksi Body Roundness Index untuk Prediabetes pada Orang Dewasa di Indonesia: Assessing the Predictive Accuracy of the Body Roundness Index for Prediabetes in Indonesian Adults - Pramono, Adriyan; Nursari, Elia Nawang; Dieny, Fillah Fithra; Kurniawati, Dewi Marfu'ah; Rahadiyanti, Ayu (Universitas Airlangga, 2025)
Background: Anthropometric measurements for identifying body fat could be used to screen individuals with prediabetic risk. Objectives: To evaluate and compare the diagnostic accuracy of body roundness index (BRI), conicity index (C-index), body mass index (BMI), waist circumference, and waist-to-height ratio (WHtR) as predictors of prediabetes in the adult population of Indonesia. Methods: This study employs a cross-sectional design and uses secondary data from the Baseline Health Research (Ind: Riskesdas) 2018. As many as 12.327 samples were subjected to descriptive analysis, and the area under the curve (AUC) was utilised to assess the diagnostic potential of anthropometric measures in predicting prediabetes. Results: The five anthropometric parameters have a very weak ability as a prediabetic predictor. The WHtR and BRI (AUCmen=0.571; AUCwomen=0.573) were significantly better than the other anthropometric parameters. In contrast, the C-index values for women (AUCwomen=0.548) were considerably lower than other anthropometric parameters. However, there was no significant difference between the C-index for men (AUCmen=0.560) and the waist circumference (AUC=0.564) and BMI (AUC=0.559) values. Conclusions: The body roundness index has the same ability to predict prediabetes with WHtR, while the C-index in women is weaker than waist circumference and BMI.